2021
DOI: 10.1108/cfri-01-2021-0010
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 pandemic and sovereign credit risk

Abstract: PurposeThe purpose of this study is to examine the effects of the coronavirus disease 2019 (COVID-19) pandemic on sovereign credit default swap (CDS) spreads using a large sample of countries.Design/methodology/approachIn this paper, the authors use a wide set of the sovereign CDS data of 78 countries. To measure the magnitude of the COVID-19 pandemic, the authors use the daily change of confirmed cases collected from Our World in Data. They use panel regressions to estimate the impact of the COVID-19 pandemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 37 publications
3
12
0
Order By: Relevance
“…The hypothesis assumed that the Covid-19 dynamics in Hungary, Poland, Russia and Slovakia moderately contribute to a country's credit risk assessment, measured by SCDS spreads. These results match those observed in previous studies, which showed that the impact of the Covid-19 pandemic on SCDS spreads is characterized by greater strength in countries with poorer healthcare infrastructure (Pan et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The hypothesis assumed that the Covid-19 dynamics in Hungary, Poland, Russia and Slovakia moderately contribute to a country's credit risk assessment, measured by SCDS spreads. These results match those observed in previous studies, which showed that the impact of the Covid-19 pandemic on SCDS spreads is characterized by greater strength in countries with poorer healthcare infrastructure (Pan et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…Based on the literature analysis, it has been shown that SCDS are used to measure a country's credit risk. It has been demonstrated that SCDS spreads are influenced not only by macroeconomic factors, such as public debt (Pyka and Czech, 2018;Pongsiri, 2015), inflation (Aizenman et al, 2013) or a risk-free interest rate (Ericsson et al, 2016), but also factors related to the development of the Covid-19 pandemic (Jinjarak et al, 2021;Daehler et al, 2021;Pan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To measure the greatness of this pandemic, we use the annual confirmed cases and annual deaths by country which collected from the Our World in Data. Our World in Data gathers coronavirus associated data from Johns Hopkins University Coronavirus Resource Center, and it adopted before by Pan et al [ 86 ].…”
Section: Methodsmentioning
confidence: 99%
“…Saif-Alyousfi [ 92 ] based on 45 CBs and 25 IBs indicate that Yemen War has a negative impact on deposits and loans of GCC banks. Pan et al [ 86 ] across 78 countries show how CR has broadened significantly in response to COVID-19. One-percent increase in COVID-19 infections leads to 0.17% increase in CR spreads.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%